Małe Punktowo-Symetryczne Drgania Ośrodka Sprężystego Odkształcającego się z Upływem Czasu - Duszczyk, B.; Wesołowski, Z. (Engineering Transactions, 1971)
A small motion is superimposed on the finite motion of a sphere with the radius increasing uniformly with time. The fundamental deformation determined, a small time-dependent displacement field is imposed on this motion. The equations to be satisfied by these small displacements are found, their trivial solutions being derived. After expanding the additional displacements into a Fourier series of spherical functions the case is considered when the solution is a product of a function of time and a function of the remaining variables. It is shown that the only possible vibrations are, in this case, radial vibrations of the sphere.A plane wave propagating in the sphere undergoing the finite deformation is considered.